Forcings and feedbacks in the GeoMIP ensemble for a reduction in solar irradiance and increase in CO2. Issue 9 (9th May 2014) - Huneeus, Nicolas; Boucher, Olivier; Alterskjær, Kari; Cole, Jason N. S.; Curry, Charles L.; Ji, Duoying; Jones, Andy; Kravitz, Ben; Kristjánsson, Jón Egill; Moore, John C.; Muri, Helene; Niemeier, Ulrike; et al.
Abstract The effective radiative forcings (including rapid adjustments) and feedbacks associated with an instantaneous quadrupling of the preindustrial CO2 concentration and a counterbalancing reduction of the solar constant are investigated in the context of the Geoengineering Model Intercomparison Project (GeoMIP). The forcing and feedback parameters of the net energy flux, as well as its different components at the top‐of‐atmosphere (TOA) and surface, were examined in 10 Earth System Models to better understand the impact of solar radiation management on the energy budget. In spite of their very different nature, the feedback parameter and its components at the TOA and surface are almost identical for the two forcing mechanisms, not only in the global mean but also in their geographical distributions. This conclusion holds for each of the individual models despite intermodel differences in how feedbacks affect the energy budget. This indicates that the climate sensitivity parameter is independent of the forcing (when measured as an effective radiative forcing). We also show the existence of a large contribution of the cloudy‐sky component to the shortwave effective radiative forcing at the TOA suggesting rapid cloud adjustments to a change in solar irradiance. In addition, the models present significant diversity in the spatial distribution of the shortwave feedback parameter in cloudy regions, indicating persistent uncertainties in cloud feedback mechanisms.